Cation exchange membranes by radiation-induced graft copolymerization of styrene onto PFA copolymer films. II. Charactarization of sulfonated graft copolymer membranes - Nasef, Mohamed Mahmoud; Saidi, Hamdani; Mohd. Nor, Hussin; Ooi, Mun Foo (2000)
PFA-g-polystyrene sulfonic acid membranes were prepared by simultaneous radiation-induced graft copolymerization of styrene onto poly(tetrafluoroethylene- co-perfluorovinyl ether) (PFA) film followed by sulfonation. The membrane physicochemical properties such as swelling behavior, ion exchange capacity, hydration number, and ionic conductivity were studied as a function of the degree of grafting. Thermal as well as chemical stability of the membranes was also investigated. The membrane properties were found to be mainly dependent upon the degree of grafting. The water uptake, ion exchange capacity, hydration number, and ionic conductivity of the membranes were increased, whereas the chemical stability decreased as the degree of grafting increased. The membranes showed reasonable physico-chemical properties compared to Nafion 117 membranes. However, their chemical stability has to be further improved to make them acceptable for practical use in electrochemical applications.